(untitled) (NUTA Journal, 2018)
A value added tax (VAT) is a tax not on the total value of the commodity being sold, but on the value added by the last trader. Developing countries are engaging in the study of VAT more seriously as it is the source of tax revenue which has high tax potential yield among the existing tax systems. In this situation, this paper intended to assess practices of VAT and VAT administration as well as its contribution on GDP in Nepalese context. More so, the study collected secondary data which are analyzed based on descriptive/comparative methods. The study found that, sales tax has been replaced by VAT since 1997 in Nepal. Before that sales tax played a vital role to collect revenue and resources mobilization. Department of VAT and its field offices were/are responsible for administering VAT functions that was/is not yet attractive and efficient. However, data shows that collecting VAT is in increasing order. In Fiscal Year 2014/15 it came to NRs. 11516 crore which was 5.42 percent of GDP, 29.60 percent of total revenue and 48.14 percent of indirect tax revenue. And the contribution of VAT as percent of GDP remained at average of 4.04 percent during the study period (2002/2003 to 2014/2015).